Nafion-AC-based asymmetric capacitive deionization. (20th January 2017) - Cai, Wenshu; Yan, Junbin; Hussin, Taimoor; Liu, Jianyun
Abstract: Activated carbon (AC) has been widely used to prepare electrode sheet for capacitive deionization (CDI) owing to its high surface area for ionic adsorption. However, further modification of the AC electrode is still necessary to improve the CDI performance by enhancing the ionic transportation inside the electrode. Here, an asymmetric CDI cell was prepared using Nafion-AC composite with low PTFE content (3.5%) as the negative electrode and AC as the positive electrode. Nafion functions not only as a binder to improve the adhesion of electrode sheet, but also as a mediator to provide an ion conductive pathway for counterions. The morphology and elemental analysis of Nafion-AC were investigated via scanning electron microscopy (SEM) and elemental mapping. The electrochemical capacitance property of the Nafion-AC electrode was studied by cyclic voltammetry (CV). The desalination capacity of the asymmetric CDI cell arrived at 10.8 mg/g, compared with the symmetric AC-based cell (6.9 mg/g). Contribution of Nafion and the corresponding mechanism were analyzed by differential capacitance tests and inverse charging. It demonstrates that in the Nafion-AC composite containing low PTFE content, the co-ion repulsion was reduced and the electrode adhesion was improved. The electrode performance has been conveniently evaluated by monitoring the variation of the charging efficiency and desalination amount with time under an appropriate charge input, which is much helpful to guide the operation process in practical CDI applications.